Environmental protection profile from Paraná’s west: From Guaíra Falls to Ilha Grande National Park (Research, Society and Development, 2021)
The Ilha Grande National Park (PARNA – Parque Nacional da Ilha Grande) was created in 1997, by the Federal Decree of September 30, 1997, adopting an environmental preservation format, the type of integral protection, in which a conservation unit excludes from its territorial limits the human presence and directs its use solely and exclusively for the purposes of scientific research, development of educational activities and environmental interpretation, recreation in contact with nature and ecological tourism. The present study aims to analyze throughout history the different formats of environmental protection conferred to the region of the extreme West of Paraná, drawing a parallel with the norms published in the Brazilian legal system and the profiles of the preservationist, conservationist and ethnoconservationist thoughts. To this end, this study used the method of bibliographic review and searching of documents and national legislation to outline the various conservation models implemented in the region. However, it appears that the environmental protection attributed to the region before the creation of PARNA in Ilha Grande assumed at certain times an extremely conservationist bias and sometimes the government implemented public policies in which natural resources were viewed only under the focus of predatory development. After the establishment of the current conservation unit in October 1997, environmental actions were guided by preservationist thinking and did not generate effective environmental protection.